EDUKASI PEMANFAATAN TANAMAN SUNGKAI SEBAGAI TANAMAN OBAT KELUARGA DI NAGARI PADANG LAWEH KECAMATAN SUNGAI PUAR KABUPATEN AGAM - Dwisari Dillasamola; Hansen Nasif; Yohannes Alen; Almahdy Almahdy; Biomechy Oktomalioputri; Azzahra Ayu Sari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Indonesia is known for its abundant natural resources. Indonesian people have traditionally used herbal plants to maintain and overcome health problems. Traditional medicine is one of the alternative methods used to cure certain diseases. One of the plants that is often used as traditional medicine in Indonesia is Sungkai (Peronema canescens Jack.). The purpose of this activity is to provide education to the community about family medicinal plants (TOGA) which play an important role in maintaining health. With the survey conducted, it is hoped that this activity can have a good impact on the community. This activity was carried out in Padang Laweh, Sungai Pua District, Agam Regency, West Sumatra. Community service in the form of location surveys, education in raising awareness of the benefits of local herbal plants as the development of family medicinal plants (TOGA). Activities were carried out in August-September which were attended by 60 local people. The results of the education programme showed an increase in community understanding about the use of family medicinal plants (TOGA). The results obtained from the questionnaire data filled in by the community show that only 55% of the total respondents know the use of family medicinal plants (TOGA) can be used to improve body health. After education, the questionnaire data increased to 70%. So that the implementation of this education is considered to be able to increase community knowledge about plants that can be used as a medicine. With the implementation of this service, it can be concluded that this survey and education activity has succeeded in increasing the knowledge and utilisation of Sungkai Plants as medicinal plants by the community in Kenagarian Padang Laweh, Sungai Puar District, Agam Regency.